2023
DOI: 10.1111/jan.15569
|View full text |Cite
|
Sign up to set email alerts
|

Extending ageing nurses' working lives: A mixed‐methods systematic review

Abstract: Aim(s):To identify, describe and assess research evidence on factors that promote working until and beyond the official retirement age among nurses.Design: A mixed-methods systematic review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…(2020) 10‐point plan or Nurmeksela et al. (2023). As suggested, older nurses and midwives should be offered flexible working opportunities tailored to their specific needs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(2020) 10‐point plan or Nurmeksela et al. (2023). As suggested, older nurses and midwives should be offered flexible working opportunities tailored to their specific needs.…”
Section: Discussionmentioning
confidence: 99%
“…Australia has introduced career transition and employment programmes for mature age workers as part of its programmes to support older workers (Australian Government, 2022). Support for older nurses and midwives could be provided through recognition and respect for experience leading to mentoring opportunities according to Chen and Gardiner (2019) and Nurmeksela et al (2023) suggest individual and flexible rostering arrangements.…”
Section: Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a study by Uthaman et al (2016) found that nurses in their 40s experienced physical limitations such as musculoskeletal disorders and chronic pain that made moving and handling and shift work challenging. Although early retirement is common in the nursing profession, many older nurses choose to work beyond retirement or pensionable age due to financial instability (Nurmeksela et al, 2022). Therefore, addressing challenges related to older nurses' continuation of practice is crucial for retaining their valuable expertise and supporting those who cannot afford to retire due to financial constraints.…”
Section: What Does This Paper Contribute To the Wider Global Community?mentioning
confidence: 99%
“…older nurses may practice in environments where relationships with younger colleagues are challenging, with unsupportive management, and inequitable access to resources. Additionally, these factors were important indicators impacting nurses' work motives, the length of their work lives and perceived organisational support as evidenced in the wider literature(Armstrong-Stassen & Ursel, 2009;Baljoon et al, 2018;Nurmeksela et al, 2022). The lack of organisational support has been found to correlate with low career satisfaction and turnover among older workers(Armstrong-Stassen & Ursel, 2009).…”
mentioning
confidence: 99%